SGLT2 inhibitors for treatment of Type 2 diabetes mellitus: Focus on Canagliflozin - Santosh Kumar Singh; A K Gupta (Wolters Kluwer Medknow Publications, 2014)
The incidence of type 2 diabetes mellitus (T2DM) is increasing worldwide. The existing therapeutic classes of antidiabetic drugs are not adequately effective in maintaining long-term glycemic control in most patients, even when used in combination. Many marketed compounds do not address relevant aspects of the disease. In addition, side effects for established therapies such as hypoglycemia and weight gain have to be controlled. One emerging novel therapeutic class of antidiabetic drugs is sodium glucose co-transporter 2 (SGLT2) inhibitors. SGLT2 accounts for 90% of the glucose reabsorption in the kidney. The SGLT2 inhibitors increase urinary excretion of glucose and lower plasma glucose levels in an insulin-independent manner. This article discusses the role of novel SGLT2 inhibitor canagliflozin in the treatment of T2DM.